2022
DOI: 10.1038/s41598-022-14242-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a biocoagulant from devilfish invasive species for the removal of contaminants in ceramic industry wastewater

Abstract: This study evaluated the effectiveness of a biocoagulant produced from the devilfish invasive species and its combination with two chemical coagulants (aluminum sulfate and ferric sulfate) to remove turbidity, chemical oxygen demand, and total suspended solids in ceramic industry wastewater using a combined experimental design of Mixture-Process. This design optimized the coagulation process and evaluated the effects and interactions between mixture components and coagulant doses. An analysis of variance was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Visible turbidity difference due to growth of microorganisms was not established as the clay molecules make the water appear turbid. In some scenarios, turbidity present in ceramic industry wastewater exceeds far beyond the World Health Organization (WHO) recommended value of less than 5 NTU (Aguilera Flores et al, 2022). Control showed no change in pH values throughout its 3-day run, suggesting that addition of consortia elevated the pH toward more alkalinity.…”
Section: Lab-scale Experimentation On Ceramic Wastewater Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Visible turbidity difference due to growth of microorganisms was not established as the clay molecules make the water appear turbid. In some scenarios, turbidity present in ceramic industry wastewater exceeds far beyond the World Health Organization (WHO) recommended value of less than 5 NTU (Aguilera Flores et al, 2022). Control showed no change in pH values throughout its 3-day run, suggesting that addition of consortia elevated the pH toward more alkalinity.…”
Section: Lab-scale Experimentation On Ceramic Wastewater Treatmentmentioning
confidence: 99%
“…Production processes such as wet beneficiation and grinding lead to a huge wastage of water (Sari Erkan, 2019). The wastewater from the ceramic industry is traditionally treated using chemical methods of coagulation and flocculation, followed by sedimentation, to reduce the turbidity and total dissolved solids (Aguilera Flores et al, 2022). In another case study as reported by Dinçer and Kargı (2000), after pH adjustment and nutrient equalization, ceramic industrial effluent from the chemical precipitation stage was analyzed and biologically treated in a laboratory size activated sludge unit with major focus on reducing the loads of COD (Dinçer & Kargı, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Ratnayaka et al [67] reported that high amounts of aluminum sulfate are more expensive than acidifying or alkalinizing the wastewater. Likewise, applying dual systems (a mixture of biocoagulants with chemical coagulants) could reduce the treatment cost associated with the chemical coagulant amount and sludge management [22]. In this sense, the best scenario would probably be (1), followed by ( 3) and (2).…”
Section: Potential Of Prickly Pear Peel Waste Biocoagulantmentioning
confidence: 99%
“…Some biocoagulants applied to remove turbidity from natural and synthetic water and wastewater have been reported with significant efficiencies, such as Uncaria tomentosa, 17.2% [13]; Aloe vera, 53.5% [14]; Quercus Branti, 63.5% [15]; Opuntia robusta, 68.7% [13]; Azadirachta indica, 73.0% [16]; Plantago ovata, 80.0% [17]; Dolichos lablab, 89.0% [18]; Moringa oleifera, 94.0% [18]; Cicer arietinum, 96.0% [18]; Jatropha curcas, 96.0% [19]; and banana pith, 98.5% [20]. Likewise, biocoagulants have been studied in dual systems as coagulant aids; they are mixed with chemical coagulants (ferric and aluminum salts) to improve their effectiveness of removing turbidity from water and reduce the amount of used chemical agents and generated sludge [9,15,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the collagen effectively reduce turbidity, and remove COD and TSS by 74, 79, and 94%, respectively. 65 Chitosan was used as a natural flocculant in the treatment of wastewater from a palm oil mill. The study found that chitosan was effective in reducing the concentration of solids and residual oil in the wastewater, with removal rates of up to 90% and 95%, respectively.…”
Section: Coagulation/flocculation Process For Industrial Wastewater T...mentioning
confidence: 99%